Using Artificial Intelligence-Based Collaborative Teaching in Media Learning - Wang, Weijun; Liu, Zhenhuan (Frontiers in Psychology, 2021)
In the advent of the 5G era, humans must not only learn the knowledge and skills of cross-border integration, but also use the breadth and efficiency of artificial intelligence (AI) technology to jointly break through current difficulties and create a happy and beautiful life. This article takes an elementary school as an example to discuss the decision-making factors for teachers to choose AI technology when the digital content of the school is imported into artificial intelligence collaborative teaching. After discussing the relevant literature, we have introduced into digital media education, and then compared the development and application of smart technology and human-computer collaborative teaching methods, and then constructed three aspects and factors that influence elementary school teachers’ choice of AI technology decision-making. There are twelve evaluation criteria in total. After the issuance of expert questionnaires and data analysis, it is found that the importance of the main aspects of the teacher's choice of AI technology decision-making factors are "collaborative tasks", "functional characteristics" and "modeling characteristics" in order, and the importance of the evaluation criteria is in order. Four names "Learning assistance", " security", "teaching observation" and "record review". The analysis results of this research will help provide reference for digital content development and individual recommendation services. In the future, we can further discuss the teaching innovation of digital media education, improve the quality of teaching, and help students improve their learning effectiveness.